Haplotype-resolved long-read sequencing reveals parent-of-origin effects of tandem-repeat variation in autism spectrum disorder - Jinchen Li; Tengfei Luo; Xue Ren; Songyu Yang; Hui Quan; Yan Zhu; Senwei Tan; Xiangbin Jia; Pei Yu; Yuanfeng Huang; Zhaowei Jiang; Xudong Xiang; et al. (Science Bulletin, 2026)

Acetic Acid Suppresses Perennial Ryegrass Growth In Vitro by Disrupting Gibberellin and Auxin Homeostasis and Restricting Cell Expansion - Hao Guan; Caiyi Xie; Weiyu Jia; Ruiting Ouyang; Yuhan Xia; Yuhan Fu; Yi Man; Huaiyang Hou; Yingjun Chi; Bin Xu; Jing Zhang (Journal of Plant Growth Regulation, 2026)

Conditional Generative Adversarial Networks Enhance Atmospheric Thermodynamic Profile Retrieval from Ground-Based Microwave Radiometer Measurements - Disong Fu; Xia Li; Jingmiao Zhu; Dazhi Yang; Ruiting Liu; Hongrong Shi; Guangyu Gao; Xinlei Han; Xiang’ao Xia; Yunjie Xia; Maoling Ayitikan; Kai Cheng; et al. (Journal of Meteorological Research, 2025)

Oligo-residual disease in metastatic ALK-positive NSCLC treated with alectinib - Xi Yang; Xiao Chu; Ruiting Ye; Jianjiao Ni; Ya Zeng; Yue Zhou; Qing Xia; Shengping Wang; Qiao Li; Shuai Liu; Zhengfei Zhu; Li Chu (Clinical & Experimental Metastasis, 2025)

Freshness Prediction of Silver Carp Using Sub-Layer Equivalent Circuit Parameters in Electrochemical Impedance Spectroscopy - Jian Sun; Ruiting Xia; Feng Lin; Kai Wu; Jinfu Chen; Gangshan Wu; Wei Pan; Tingting Zou (Journal of Aquatic Food Product Technology, 2025)

Nebulization Therapy with Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes for COVID-19 Pneumonia - Meiping Chu; Hao Wang; Linjie Bian; Jiehui Huang; Danping Wu; Ruiting Zhang; Fangli Fei; Yigang Chen; Jiazeng Xia (Stem Cell Reviews and Reports, 2022)
Background Scientists have been facing numerous challenges in the development of an effective therapeutic strategy for the treatment of COVID-19 pneumonia. Several studies have suggested that improving patient immunity and reducing lung injury induced by SARS-CoV-2 may be effective for treating patients with COVID-19. Methods A pilot trial of nebulization therapy with exosomes of mesenchymal stem cells (MSCs) was performed on seven patients with COVID-19 pneumonia. Exosomes secreted from MSCs were collected and purified using multiple ultrafiltration steps. All patients were treated with nebulization of MSC-derived exosomes, and primary safety and efficacy outcomes were evaluated. Results Our clinical study demonstrated that nebulization of MSC-derived exosomes is a novel method that might be utilized in the treatment of COVID-19 pneumonia. Nebulization of MSC-derived exosomes did not induce acute allergic or secondary allergic reactions but did promote the absorption of pulmonary lesions and reduce the duration of hospitalization for mild cases of COVID-19 pneumonia. Conclusions Nebulization of MSC-derived exosomes is a safe, effective, and simple method, and their application at the beginning of treatment may be more beneficial. Trial Registration Chinese Clinical Trial Registry, ChiCTR2000030261. Registered on 26 February 2020. Graphical Abstract

A one-step ligation system for rapid generation of armed, conditionally-replicating adenoviruses - Xing Li; Ruiting Xia; Jing Zhao; Dongyang Wang; Qinwen Mao; Haibin Xia (Biotechnology Letters, 2013)